A proposal to implement a carbon tax in Algeria: A closer look at Sweden's world-leading experience - Dahdouh, Nabil; Boubaya, Hacene; Afeissa, Abderrahmane (International journal of economic perspectives, 2025)
The aim of this study is to provide an objective reading of the proposed implementation of a carbon tax in Algeria as a tool to reduce carbon emissions. This study explores the nature of carbon taxes, the determinants of their design, the selection of an appropriate price, the justifications for their imposition, and their economic impact on Algeria. It also examines their importance in reducing carbon emissions, which pollute the environment. Despite the positives of this type of tax, it has negative effects on economic growth and international competitiveness in the short term. The research paper, through a close examination of Sweden's experience in imposing carbon taxes on companies and households, demonstrates the impact of carbon taxes on fossil fuels used in transportation, heating, and production processes, and the resulting reduction in carbon emissions while maintaining a strong economy.